PENGGUNAAN VIDEO PEMBELAJARAN SEBAGAI STRATEGI PENINGKATAN EFEKTIVITAS PEMBELAJARAN PJBL KURIKULUM MERDEKA - Adillia Natasya Saputri; Citra Firdani; Nurcholif Diah Sri Lestari; Dian Kurniati; Erfan Yudianto (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Merdeka curriculum emphasizes student centered learning that cultivates creativity, independence, and critical thinking skills. One of the learning models aligned with these principles is Project Based Learning (PjBL). However, the implementation of PjBL at the junior high school level still encounters several challenges, particularly the limited availability of learning resources and students insufficient conceptual understanding of the material. This study aims to analyze the effectiveness of using instructional videos as a supporting medium in implementing the PjBL model. Method employed in this study is a literature review of previous research relevant to the integration of instructional videos within the PjBL framework. The findings indicate that the use of instructional videos enhances students’ learning motivation, deepens conceptual understanding, and fosters active participation in project activities. Furthermore, instructional videos promote independent and collaborative learning, aligning with the core principles of the merdeka curriculum. Therefore, instructional videos play a significant role in improving the effectiveness of PjBL implementation at the junior high school level.